2018
DOI: 10.5213/inj.1834904.452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Alpha-Blocker for the Treatment of Nonneurogenic Voiding Dysfunction in Women: An 8-Week, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: PurposeTo evaluate the efficacy of an alpha-1 adrenergic receptor (α1-AR) blocker for the treatment of female voiding dysfunction (FVD) through a pressure-flow study.MethodsThis was a randomized, double-blind, placebo-controlled trial. Women aged ≥18 years with voiding symptoms, as defined by an American Urological Association symptom score (AUA-SS) ≥15 and a maximum flow rate (Qmax) <15 mL/sec with a voided volume of >100 mL and/or a postvoid residual (PVR) volume >150 mL, were randomly allocated to either th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 19 publications
0
26
0
13
Order By: Relevance
“…The authors in the present study compared adverse event rates between α1-blockers and placebo in the studies that reported safety outcomes for the α1-blockers and found no statistically significant difference in the adverse event rate of the α1-blockers compared to placebo [5,6,25,26]. The side effects of α1-blockers reported in the studies were dizziness, headache, asthenia, GI discomfort, and edema.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The authors in the present study compared adverse event rates between α1-blockers and placebo in the studies that reported safety outcomes for the α1-blockers and found no statistically significant difference in the adverse event rate of the α1-blockers compared to placebo [5,6,25,26]. The side effects of α1-blockers reported in the studies were dizziness, headache, asthenia, GI discomfort, and edema.…”
Section: Discussionmentioning
confidence: 70%
“…Subsequently, title and abstract review eliminated 377 articles, with only trials published in English included in the present study. An analysis of the remaining full-text articles with respect to the inclusion criteria resulted in the final selection of 14 studies (Table 1) with a total of 1,319 patients [5,6,16-27]. Of these studies, 6 were RCTs and 8 were open-label prospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations